2023
DOI: 10.1371/journal.pone.0280985
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, beliefs and practices towards HIV/AIDS among adolescents in India: A scoping review protocol

Abstract: Introduction Acquired Immune Deficiency Syndrome (AIDS) is a major health concern among Indian adolescents (10–19 years). Indian adolescents lack adequate knowledge about HIV/AIDS and adopt wrong practices. The present scoping review aims to understand the status of knowledge, beliefs and practices among Indian adolescents about HIV or HIV/AIDS. The present study will also focus on their understanding and the source of knowledge and awareness regarding HIV/AIDS. Methodology The recommendations of Arksey and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Education is given more importance in the fight against HIV/AIDS as school-going children and young adolescents are still forming their beliefs and the prevalence of the disease is incredibly low, thus instilling good practices in them would lead to a population which has higher knowledge and awareness. 16 As our study population includes school-going children, it is expected that they are receiving a basic level of education in their science classes. This helps us to determine the effectiveness of present education systems and we can suggest necessary changes.…”
Section: Discussionmentioning
confidence: 99%
“…Education is given more importance in the fight against HIV/AIDS as school-going children and young adolescents are still forming their beliefs and the prevalence of the disease is incredibly low, thus instilling good practices in them would lead to a population which has higher knowledge and awareness. 16 As our study population includes school-going children, it is expected that they are receiving a basic level of education in their science classes. This helps us to determine the effectiveness of present education systems and we can suggest necessary changes.…”
Section: Discussionmentioning
confidence: 99%
“…There has been limited research on adolescent and young populations/non-key populations and their vulnerability to HIV risks. To the best of our knowledge, no other literature reviews are available on this topic except a study protocol published by Patsani et al [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 A previous study reported that India has the highest number of adolescent HIV infections in Southeast Asia, which is really a cause for concern. 7 Adolescence is a transition phase from being a child to becoming an adult. And due to this, they require the utmost care and attention from both parents and society.…”
Section: Introductionmentioning
confidence: 99%